Environmental and economic assessment of gas production from gas hydrate reserves in Krishna-Godavari basin in the Indian offshore. (March 2023) - Majumdar, Dibyarup; Gupta, Manish; Shastri, Yogendra; Mahajani, Sanjay M.
Graphical abstract: Highlights: Sustainability of gas hydrate recovery in Indian offshore is studied. Cradle-to-gate LCA and techno-economic analysis is performed. The life cycle impact found to be 1.038 kg CO2 eq. per kg of gas. Significant climate change reduction benefits possible from gas hydrates. Long-term economic outlook positive providing import reduction opportunities. Abstract: Large quantities of natural gas hydrate reserves and their proximity to the Indian onshore make them a potentially sustainable energy source for India in future. This paper presents an environmental impact study of the dissociation of gas hydrates in Indian off-shore through life-cycle assessment (LCA). Using the cradle-to-gate scope, this work performs detailed LCA for natural gas obtained from gas hydrates. The results of this study show that the climate change impact is 1.038 kg per kg of natural gas. Replacing imported natural gas with gas obtained from hydrate dissociation can save around 41.3 million tonnes CO2 (62 %) emissions. The contribution of this estimated emission savings to the pledge taken by the Indian government of reducing emissions by 1 billion tonnes by the year 2030 is also looked into. A sensitivity analysis has also been done to identify the critical parameters influencing the study. Furthermore, this paper discusses the dynamics of economic feasibility through scenarios of replacing current Indian conventional imports (Liquefied natural gas (LNG) through sea transportation) with gas from hydrate reserves. The economic analysis indicates a saving of about 25 USD/MMBTU for replacing a part of the current LNG imports purchased at volatile spot prices.